Haiti Acute and Emergency Care Conference: descriptive analysis of an acute care continuing medical education program - Losonczy, Lia I; Williams, Sarah; Papali, Alfred; Costantino, Corey A; Colas, L Nathalie; Patel, Bhavesh M; Zimmer, Donald F; Olwine, Shannon R; Davidson, Zena; Wilson, John W; McCurdy, Michael T; Augustin, Marc E; et al. (Journal of global health reports, 2019)
# Background Several disasters over the past decade have highlighted the need for strong acute-care systems in Haiti. As part of a multifaceted approach to improving national acute-care training, the Research and Education consortium for Acute Care in Haiti (REACH) launched the inaugural Haiti Acute and Emergency Care Conference (HAECC). # Methods REACH is a Haitian-led, multinational collaboration based out of Saint Lûc Hospital in Port-au-Prince. The first HAECC was held in April, 2017. Pre- and post-course evaluation consisted of subjective and objective components. Differences between pre- and post-responses were determined using McNemar's test of paired proportions. # Results 57 participants from 21 hospitals in five Haitian departments were included. The majority (37/58, 63.8%) were physicians. Most (33/57, 57.9%) had no prior training in acute or emergency care, but 8/57 (14.0%) had taken ATLS/ACLS, 11/57 (19.3%) had taken a formal course not internationally recognized, and only 1/57 (1.8%) had completed acute care specialty training. 43.7% (25/57) reported routine access to point-of-care ultrasound. Following course completion, participants felt significantly more comfortable managing basic emergency conditions (up to 25/57, 43.9% increase, *P*\<0.01) and using ultrasound (up to 30/57, 52.6% increase, *P*\<0.01), but improvements on objective testing were not significant (ranging from -2 (-3.5%, *P*=1.00) to +5 (8.7%, *P*=0.15) change). # Conclusions While continued quality review is necessary for future iterations of the conference, the inaugural HAECC provided a useful "first pass" for current front-line providers in Haiti.